Comparative study of Indrani Vough manufactured in the laboratory and collected from sweet meat shops of Dinajpur district (Bangladesh Journal of Animal Science, 2013)
This experiment was conducted to evaluate the quality of Indrani vough prepared in the laboratory and collected from Dinajpur district. Four types of Indrani vough samples were used in this experiment. Laboratory made Indrani vough was assigned as A sample. B, C and D samples were collected from Shananda sweet meat , Pabna sweet meat and Jalozogh sweet meat shop respectively. All the samples were tested for organoleptic, chemical and microbiological parameters. Among organoleptic parameters such as body and texture, color and appearance, and taste score of four types of samples differed insignificantly, but quality of samples differed significantly for flavour score (p